(untitled) (Bangladesh Journal of Medical Science, 2013)
This paper highlights the fact that many anterior teeth requiring restoration are severely weakened, having wide flared canal spaces and thin dentinal walls, and are at a high risk of getting fractured. An 20 year old female patient reported with the complaint of unesthetic smile due to fracture and discolored tooth. She gave a history of trauma around 4-5 years back. This case was managed by the customization of fiber reinforced posts which has made a great impact on esthetics and redistribution of stresses along the radicular space and dentin tissue conservation. Thus modern techniques reflect a change from what was once considered prosthodontic procedure to one which marries endodontic principles with sound understanding of mechanical objectives. DOI: http://dx.doi.org/10.3329/bjms.v12i1.13359 Bangladesh Journal of Medical Science Vol. 12 No. 01 January13 pp.100-103